Mutagenesis Of Microbial Transglutaminase For QTAG-KTAG Conjugation - Chan, Soo Khim (2018)
The initial discovery of microbial transglutaminase (mTGase) was to soothe the high cost of mammalian transglutaminase in food processing industries. This enzyme has become an important tool in biotechnological applications due to its robustness, availability in high purity, bypass the need of calcium ions for activation and high reaction rate. However, mTGase has low substrate specificity due to its wide active site cleft which impeding its diverse applications in biotechnological use. Therefore, mutagenesis of mTGase to obtain substrate specific enzyme is highly desirable for site-specific conjugations.